2016
DOI: 10.1093/jac/dkw265
|View full text |Cite
|
Sign up to set email alerts
|

Virological efficacy of PI monotherapy for HIV-1 in clinical practice

Abstract: BackgroundClinical trials of PI monotherapy indicate that most participants maintain viral suppression and emergent protease resistance is rare. However, outcomes among patients receiving PI monotherapy for clinical reasons, such as toxicity or adherence issues, are less well studied.MethodsAn observational study of patients attending an HIV treatment centre in London, UK, who had received PI monotherapy between 2004 and 2013, was conducted using prospectively collected clinical data and genotypic resistance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The interpretation of the association between CSF escape/discordance and bPI is unclear, as the rationale for bPI monotherapy use in select patients may be a confounder. Patients who are given bPI monotherapy may be poorly-adherent and bPI is used due to its high barrier to resistance [ 59 ] or may be ill patients and bPI monotherapy is used in order to minimise drug interactions [ 60 ] or may have experienced toxicity from NRTIs and bPI is used as a temporary measure [ 61 ]. Boosted PI-based therapy may represent poor adherence, extensive ART experience and the opportunity for the virus to have evolved under drug pressure.…”
Section: The Spectrum Of Csf Escape/discordancementioning
confidence: 99%
“…The interpretation of the association between CSF escape/discordance and bPI is unclear, as the rationale for bPI monotherapy use in select patients may be a confounder. Patients who are given bPI monotherapy may be poorly-adherent and bPI is used due to its high barrier to resistance [ 59 ] or may be ill patients and bPI monotherapy is used in order to minimise drug interactions [ 60 ] or may have experienced toxicity from NRTIs and bPI is used as a temporary measure [ 61 ]. Boosted PI-based therapy may represent poor adherence, extensive ART experience and the opportunity for the virus to have evolved under drug pressure.…”
Section: The Spectrum Of Csf Escape/discordancementioning
confidence: 99%
“…The MONET [21], MONOI [25], PROTEA [20] and PIVOT [26] trials have shown that DRV/r monotherapy can be considered as a treatment option for patients with stable virological suppression on combination therapy (HIV-1 RNA <50 copies/mL for at least six months). DRV/r monotherapy has also recently been reported to exhibit a good efficacy and safety profile in routine clinical practice [14,15,27]. In this cohort, DRV/r QD monotherapy was well tolerated, adverse events were mainly GI related as observed in the MONET and PROTEA monotherapy trials [20,28] as well as in another real world study from Spain [14].…”
Section: Discussionmentioning
confidence: 52%
“…Concerns persist about virologic escape in the CSF and the development of CNS disease in subjects receiving PI monotherapy, and this combination is not recommended in HBV coinfection. In addition, real-world studies report a higher incidence of virological failure and emergent resistance than has been described in clinical trials (16).…”
Section: Treatment Experiencedmentioning
confidence: 96%